On the problem of the qualification of the object and the subject of crimes that infringe on the environmental safety. (Journal of actual problems of jurisprudence, 2016)
The scientific article from the theoretical point of view, the author considers the problem of qualification of the object and the subject of crimes that infringe on the environmental safety. Given the author’s classification of the subject crimes encroaching on environmental safety. A complete classification of the object crimes encroaching on environmental safety, a dedicated kinds of objects – environmental safety. Also for proper qualification of the object and the subject of crimes that infringe on the environmental safety, are ways to improve the criminal law.
Keywords: environmental crime; environmental security; the object of the crime; the qualification of crimes